Effect of Carya illinoinensis, Quercus rubra and Smilax glyciphylla extracts, pectin, and papain on the dental biofilm microorganisms - Elda P. Segura; Luis Méndez; Eréndira Márquez; Alejandra I. Vargas; Karla M. Gregorio; José L. Martínez; Anna Ilyina (GarVal Editorial Ltda., 2015)
Context: Dental caries is an infectious disease resulting in destruction of tooth structure by acid-forming bacteria found in dental plaque and intraoral biofilms, which are made up of mixed-species microbial communities, and their uncontrolled outgrowth can lead to oral disease. Aims: To analyze new biological materials (papain, pectin, three plant extracts and their combinations), for prevention, control, and treatment of oral bacteria and biofilm in vitro and in vivo. Methods: Papain, citric pectin, extracts of Carya illinoinensis, Quercus rubra, and Smilax glyciphylla were applied. In vitro test was performed by means of the spectrophotometric assay and CFU evaluation after treatments application. In vivo tests were performed to evaluate the number of microorganisms presented in dental biofilm: before and 1.5 h after brushing with different treatments; after 10 days of brushing with various treatments in 10 groups of patients, signing an informed consent approved by the Institutional Ethics Committee of the Autonomous University of Coahuila. Results: In vitro, the plant extracts inhibited the growth of Streptococcus sp. as well as a mixture of microorganisms that form dental biofilms. Papain activity was inhibited by plant extracts. In vivo, brushing of teeth with selected plant extracts reduced the number of bacteria in the dental plaques. Conclusions: The extracts of Quercus rubra, Carya illinoinensis and Smilax glyciphylla and papain (with or without pectin) had an inhibitory effect on the dental biofilm formation. In vitro test demonstrated the bacteriostatic effect of plant extracts or their mixture.